1994
DOI: 10.1093/treephys/14.5.467
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the aboveground respiration of hinoki cypress (Chamaecyparis obtusa) on tree size

Abstract: Nighttime respiration was measured at monthly intervals over one year on the aboveground parts of five sample trees in an 8-year-old hinoki cypress (Chamaecyparis obtusa (Sieb. et Zucc.) Endl.) stand, by an enclosed standing-tree method. The respiration rate rose rapidly from early spring to a maximum in June, and decreased abruptly in July and then gradually toward autumn and winter. The seasonal change in the respiration rate was synchronized with stem volume increment rather than with monthly mean air tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
0
22
1
Order By: Relevance
“…The exponent f has been controversial, and various values have been reported based on studies of both animals and plants (15). Recently, it was suggested that f = 1 for relatively small plants, based on data for a 10 6 -fold range of body mass (16), including measurements using a whole-plant chamber (18,19). If f = 1, this means that whole-plant respiration scales isometrically with body mass, which may be reasonable in the case of herbaceous plants and small trees because nearly all of their cells, even those in the stems, should be active in respiration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The exponent f has been controversial, and various values have been reported based on studies of both animals and plants (15). Recently, it was suggested that f = 1 for relatively small plants, based on data for a 10 6 -fold range of body mass (16), including measurements using a whole-plant chamber (18,19). If f = 1, this means that whole-plant respiration scales isometrically with body mass, which may be reasonable in the case of herbaceous plants and small trees because nearly all of their cells, even those in the stems, should be active in respiration.…”
mentioning
confidence: 99%
“…Most data on whole-plant respiration have been acquired using indirect methods of estimation, limited to small plants, or focused on a narrow range of body sizes (2,5,15,16,18,19,(23)(24)(25)(26). Furthermore, most studies of plant metabolic scaling have been based on the aboveground parts and have ignored respiration of the roots, which is very difficult to measure (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The respiration was nondestructively measured monthly throughout a year (from May 2007 to April 2008) with a modified enclosed standing tree method (cf. Ninomiya & Hozumi 1983a, Yokota et al 1994. The aerial parts of each sample tree were enclosed in a cylindrical chamber made of 0.1 to 0.2 mm thick polyvinyl chloride film.…”
Section: Methodsmentioning
confidence: 99%
“…bankruptcy (Yokota & Hagihara 1996). On the other hand, Ninomiya & Hozumi (1981), Ogawa et al (1985) and Yokota et al (1994) all found that the annual respiration of individual trees is proportional to their mass in young conifer stands (<10 yr old). In a broad summary of studies covering many species, Reich et al (2006) also showed that whole-plant respiration rate scales are approximately proportional to total mass.…”
Section: Size-dependence Of Metabolismmentioning
confidence: 99%